2003
DOI: 10.1084/jem.20021726
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Prediction of Survival in Patients with the Leukemic Phase of Cutaneous T Cell Lymphoma

Abstract: We have used cDNA arrays to investigate gene expression patterns in peripheral blood mononuclear cells from patients with leukemic forms of cutaneous T cell lymphoma, primarily Sezary syndrome (SS). When expression data for patients with high blood tumor burden (Sezary cells >60% of the lymphocytes) and healthy controls are compared by Student's t test, at P < 0.01, we find 385 genes to be differentially expressed. Highly overexpressed genes include Th2 cells–specific transcription factors Gata-3 and Jun B, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
177
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(194 citation statements)
references
References 51 publications
11
177
2
4
Order By: Relevance
“…Of note, MF/SS is associated with the expression of Th2-associated genes (e.g., GATA-3) and the production of Th2-associated cytokines (e.g., IL-4, IL-5, and IL-10), thus raising the possibility that a significant subset of patients may harbor Th2-derived clones [32][33][34][35][36]. As the cell of origin is further defined in subsets of CTCL, including MF/SS, one may anticipate that this data may have a significant impact on the classification, risk-stratification, and treatment of these diseases.…”
Section: Cell Of Originmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, MF/SS is associated with the expression of Th2-associated genes (e.g., GATA-3) and the production of Th2-associated cytokines (e.g., IL-4, IL-5, and IL-10), thus raising the possibility that a significant subset of patients may harbor Th2-derived clones [32][33][34][35][36]. As the cell of origin is further defined in subsets of CTCL, including MF/SS, one may anticipate that this data may have a significant impact on the classification, risk-stratification, and treatment of these diseases.…”
Section: Cell Of Originmentioning
confidence: 99%
“…Cyclin upregulation, including cyclinD1, and loss of RB1 have also been described [94]. As gene-expression profiling and nextgeneration sequencing technologies are used, additional pathogenic pathways, including those involving transcription factors regulating T-cell differentiation [35,36], c-MYC [95,96], RAS/RAF/MEK signaling [97], among others [90,98], may be identified in subsets of CTCL.…”
Section: Immunopathogenesismentioning
confidence: 99%
“…Samples of total RNA were linearly amplified with Illumina TotalPrep RNA Amplification Kit (Ambion), and 1.6 g of the amplified RNA was labeled with 65 Ci of [ 33 P]dCTP as previously described (20). All RNA samples were amplified, labeled, and hybridized in the same batch.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of several B-NHLs series has led to the definition of molecular subgroups with specific outcomes (Alizadeh et al, 2000;Rosenwald et al, 2002;Shipp et al, 2002;Thieblemont et al, 2004). In contrast, only a limited number of T-cell neoplasms have been investigated using microarrays, including mycosis fungoides (Tracey et al, 2003), leukemic phase of cutaneous T-NHL (Kari et al, 2003), cell lines derived from T-cell malignancies (Li et al, 2001;Fillmore et al, 2002), or PTCL (Martinez-Delgado et al, 2004). A recent profiling analysis was focused on the comparison between PTCL and T-lymphoblastic lymphoma (T-LBL) types (Martinez-Delgado et al, 2004), but a molecular classification of PTCL entities has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%